2022
DOI: 10.1111/raq.12677
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic diversity in marine and freshwater recirculating aquaculture systems

Abstract: Intensive aquaculture food production has been continually increasing over the past decades. Recirculating aquaculture is an innovative technology which relies on water reuse and removal of toxic metabolites by utilizing specific prokaryotic groups such as nitrifiers, settled in special biofilters. Focused on recent next generation sequencing-based studies on the microbiome of recirculating aquaculture systems, this review highlights dominant genera and families, and investigates their possible metabolic funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 176 publications
(366 reference statements)
0
17
0
Order By: Relevance
“…Microbiome in the rearing water comprised three main phyla: Proteobacteria, Bacteroidetes, and Verrucomicrobia (maximum of 95.1, 75.8, and 58.4%, respectively, Figure S2). Such a bacterial composition has been commonly observed, in which a recent review reported that Proteobacteria and Bacteroidetes are the top two phyla in their abundance for RAS regardless of the rearing fish species . In addition, some studies have reported the dominance of Verrucomicrobia followed by Proteobacteria and Bacteroidetes in aquaculture systems. , The GLM suggested that the proportion of Proteobacteria and Bacteroidetes did not differ among fish types, whereas that of Verrucomicrobia in the G.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Microbiome in the rearing water comprised three main phyla: Proteobacteria, Bacteroidetes, and Verrucomicrobia (maximum of 95.1, 75.8, and 58.4%, respectively, Figure S2). Such a bacterial composition has been commonly observed, in which a recent review reported that Proteobacteria and Bacteroidetes are the top two phyla in their abundance for RAS regardless of the rearing fish species . In addition, some studies have reported the dominance of Verrucomicrobia followed by Proteobacteria and Bacteroidetes in aquaculture systems. , The GLM suggested that the proportion of Proteobacteria and Bacteroidetes did not differ among fish types, whereas that of Verrucomicrobia in the G.…”
Section: Resultsmentioning
confidence: 74%
“…Such a bacterial composition has been commonly observed, in which a recent review reported that Proteobacteria and Bacteroidetes are the top two phyla in their abundance for RAS regardless of the rearing fish species. 20 In addition, some studies have reported the dominance of Verrucomicrobia followed by Proteobacteria and Bacteroidetes in aquaculture systems. 21 , 22 The GLM suggested that the proportion of Proteobacteria and Bacteroidetes did not differ among fish types, whereas that of Verrucomicrobia in the G. punctata tank was larger ( Table S1 ), suggesting that Verrucomicrobia might be a more host-specific phylum in the rearing water.…”
Section: Resultsmentioning
confidence: 99%
“…These communities are often actively maintained in the biofilter section of the system, which is designed to maximize the surface area with sand, granulated active carbon, or synthetic carrier material, and perform an array of services, such as removing toxic metabolic products (e.g., ammonia, nitrite, nitrate, sulfide, and sulfate), and organic waste. Prominent representatives of the oxidizing ammonia genera found in RAS are, for example, Nitrosomonas , Nitrosospharea , and Nitrosospira [13], as well as ammonia-oxidizing archaea and Nitrotoga species [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Fish-related disease outbreaks threaten the livelihood of farmers and food security [16] and incur an estimated $6 billion loss yearly [17] as a result of stock loss. Also, water-associated off-flavoring bacterial groups may adversely impact the quality of the final product [13]. Various management approaches, such as cleaning and disinfection, aim to reduce opportunistic pathogen species such as Aeromonas or Flavobacterium [18] but could potentially open niches for pathogenic species and promote undifferentiated microbial growth.…”
Section: Introductionmentioning
confidence: 99%
“…Fish-related disease outbreaks threaten the livelihood of farmers and food security [16] and incur an estimated $6 billion loss yearly [17] as a result of stock loss. Also, waterassociated off-avoring bacterial groups may adversely impact the quality of the nal product [13]. Various management approaches, such as cleaning and disinfection, aim to reduce opportunistic pathogen species such as Aeromonas or Flavobacterium [18] but could potentially open niches for pathogenic species and promote undifferentiated microbial growth.Accordingly, managing the microbial communities that maintain water quality in RAS poses complex challenges.…”
mentioning
confidence: 99%